Perencanaan Peningkatan Kualitas SDM dalam Upaya Pengembangan UMKM - Umi Latifah; Husnurrosyidah; Wulandari Dyah Suryanti (Program Studi Ekonomi Syariah IAIN Parepare, 2023)
This study aims to carry out a systematic review of planning to improve the quality of appropriate human resources in an effort to develop MSMEs in Pati Regency where quality human resources will be able to generate ideas, creativity, leadership skills and the courage to open up potential opportunities for MSMEs. This research uses descriptive qualitative research with snowball sampling method. The results of the study indicate that there are problems faced by business actors in the Micro, Small and Medium Enterprises cluster in Pati Regency, including aspects of capital, production, technology, marketing, human resources, bureaucracy, facilities and infrastructure, as well as social and economic aspects. In addition, the right strategy for developing. MSMEs in Pati Regency is the SO (Growth) Strategy. SO (Growth) strategy is a strategy that utilizes existing strengths to increase competitive advantage. MSMEs need to take more advantage of access to capital through related agencies such as Regional Innovation SIPENCAR (Synergy of Planning Assistance Through Clusters). SIPENCAR Bappeda oversees and ensures that from a planning standpoint, in the synergy of OPD planning assistance, the main tasks and functions overlap with MSME assistance. So that the OPD as mentioned above allocates its budget in planning documents to assist and facilitate MSMEs hoping that MSMEs can upgrade so that they can improve the people's economy.